Pedagogy of Equality in the Family, Schools, and Society: Self-Reflection as Muslim Feminist in Aisyiyah - Qibtiyah, Alimatul (Yayasan Jurnal Perempuan, 2016)
Feminist pedagogy is one of strategies to reach gender equality in education process whether in the family, school or society. Implementing feminist pedagogy not only benefits women’s lives better but also men’s as well as childrens’ lives. For me, feminist pedagogy and the struggle of gender equality is not only just as a slogan but it must be implemented on daily basis. This paper explores my experiences in implementing feminist pedagogy in family, school, and community. I argues that every single experience is worthy and recogined as a theory. This article is based on library research and a reflection from my experiences. The author has been marriage for 19 years, become a lecturer for 20 years and been involved as a woman activist for 23 years in Muhammadiyah’s woman organization, Aisyiyah. In every implementation of feminist pedagogy, I face challenges from audiences which relates to a variety of gender thought in the society. Based on testimonies from my spouse, students also audiences, it can be cocluded that the implementation of feminist pedagogy lead to the convenience in the process of transferring knowledge. It also contributes to change their perspective into Islamic progressive thought.